Pengaruh kandungan alumina terhadap kekasaran permukaan dan foto mikro permesinan pada komposit Al-Al2O3 - Ahmad Ibnu Nafili; Sri Mulyo Bondan Respati; Budi Santoso (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
The aluminum is the most abundant element on the earth and there are always a combination with other the elements. One of the most widely used the composite types in various applications is the Al-Al203 composite. This composite is the development of metal matrix composite ie the aluminum, with the alumina (Al2O3) as the amplifier phase. To produce a superior cast product using the recyclable materials can be done by the squeeze casting method. The squeeze casting is often called the liquid metal forging. The liquid metal compaction process is carried out in a hydraulically pressed mold. This study aims to study the effect of the alumina on the surface roughness due to machining of the squeeze casting with the variation of the alumina mixture of 5. 10. and 15% by weight. The mold is heated to a temperature of 200ï‚°C and with a hydraulic pressure of 100 MPa. From the results of roughness testing of 5. 10. and 15% wt of the alumina, having a successive the roughness of 1.10, 1.16, and 1.27 Ra. This suggests that the higher the alumina mixture the higher the roughness value but in the micro-photograph also shows more the defects.